(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article is dedicated to the clinical manifestations, diagnosis, and treatment methods of myocarditis in children. Myocarditis is an inflammatory disease of the myocardium caused by various etiologies, potentially leading to cardiac dysfunction. The study highlights the primary causes of myocarditis in children, including viral, bacterial, immunological, toxic, and drug-induced factors. The article provides an in-depth analysis of the pathogenesis, clinical classification, symptoms, and diagnostic approaches to the disease. Treatment strategies, including etiological, pathogenetic, and symptomatic therapies, are discussed. The importance of early detection and adequate treatment of myocarditis is emphasized to prevent its adverse outcomes.